2009
DOI: 10.14310/horm.2002.1230
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic sleeve gastrectomy in morbidly obese patients. Technique and short term results

Abstract: OBJECTIVE: To evaluate the efficacy of Laparoscopic Sleeve Gastrectomy (LSG) as a definitive procedure for morbidly obese patients. DESIGN: This constitutes a prospective study carried out in a tertiary care private hospital and included 15 morbidly obese patients who underwent LSG. The operation was performed through two 12 mm and two 5 mm ports, using the Endo-GIA stapler to create a lesser curve gastric tube over a 36-Fr bougie. RESULTS: Operative time, complication rates, hospital length of stay, Body Mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 18 publications
0
4
0
3
Order By: Relevance
“…Because nearly 80% of the stomach is transected and nutrients rapidly pass through a gastric conduit, increased GLP-1 and PYY 3–36 and decreased ghrelin levels result, producing key metabolic effects (78 [EL 1, RCT]; 82 [EL 1, RCT]; 83 [EL 2, PCS]; 84 [EL 2, NRCT]; 88 [EL 1, RCT]). In addition to many recently published case series reporting the short- and medium- term safety and efficacy (weight loss and glycemic status) of the SG, the majority of which were performed laparoscopically (89 [EL 3, SS]; 90 [EL 3, SS]; 91 [EL 2, PCS]; 92 [EL 3, SS]; 93 [EL 3, SS]; 94 [EL 3, SS]; 95 [EL 2, PCS]; 96 [EL 3, SS]; 97 [EL 2, PCS]; 98 [EL 2, PCS]; 99 [EL 3, SS]; 100 [EL 3, SS]; 101 [EL 3, SS]; 102 [EL 2, PCS]), there are now several comparative studies (103 [EL ]; 104 [EL ]; 105 [EL ]; 106 [EL ]; 107 [EL ]; 108 [EL ]; 109 [EL ]; 110 [EL ]; 111 [EL ]; 112 [EL ]; 113 [EL ]; 114 [EL ]; 115 [EL ]), 6 randomized controlled trials (78 [EL 1, RCT]; 82 [EL 1, RCT]; 116 [EL 1, RCT]; 117 [EL 1, RCT]; 118 [EL 1, RCT]; 119 [EL 1, RCT]), and meta-analyses (120 [EL 2, MNRCT]; 121 [EL 2, MNRCT]) demonstrating equivalency or superiority to other accepted procedures (RYGB and LAGB). Analyses of outcomes from large prospective databases have revealed a risk/benefit profile for LSG that is positioned between the LAGB and RYGB (122 [EL 3, SS]; 123 [EL 3, SS]).…”
Section: Evidence Basementioning
confidence: 99%
“…Because nearly 80% of the stomach is transected and nutrients rapidly pass through a gastric conduit, increased GLP-1 and PYY 3–36 and decreased ghrelin levels result, producing key metabolic effects (78 [EL 1, RCT]; 82 [EL 1, RCT]; 83 [EL 2, PCS]; 84 [EL 2, NRCT]; 88 [EL 1, RCT]). In addition to many recently published case series reporting the short- and medium- term safety and efficacy (weight loss and glycemic status) of the SG, the majority of which were performed laparoscopically (89 [EL 3, SS]; 90 [EL 3, SS]; 91 [EL 2, PCS]; 92 [EL 3, SS]; 93 [EL 3, SS]; 94 [EL 3, SS]; 95 [EL 2, PCS]; 96 [EL 3, SS]; 97 [EL 2, PCS]; 98 [EL 2, PCS]; 99 [EL 3, SS]; 100 [EL 3, SS]; 101 [EL 3, SS]; 102 [EL 2, PCS]), there are now several comparative studies (103 [EL ]; 104 [EL ]; 105 [EL ]; 106 [EL ]; 107 [EL ]; 108 [EL ]; 109 [EL ]; 110 [EL ]; 111 [EL ]; 112 [EL ]; 113 [EL ]; 114 [EL ]; 115 [EL ]), 6 randomized controlled trials (78 [EL 1, RCT]; 82 [EL 1, RCT]; 116 [EL 1, RCT]; 117 [EL 1, RCT]; 118 [EL 1, RCT]; 119 [EL 1, RCT]), and meta-analyses (120 [EL 2, MNRCT]; 121 [EL 2, MNRCT]) demonstrating equivalency or superiority to other accepted procedures (RYGB and LAGB). Analyses of outcomes from large prospective databases have revealed a risk/benefit profile for LSG that is positioned between the LAGB and RYGB (122 [EL 3, SS]; 123 [EL 3, SS]).…”
Section: Evidence Basementioning
confidence: 99%
“…Metabolically, it is assumed that resection of the gastric fundus also extensively removes ghrelin production. Since ghrelin induces feelings of hunger in the central nervous system (arcuate nucleus), the removal of ghrelin-producing cells induces changes in the eating behavior [ 23 , 24 , 25 ]. Valid studies have shown that it is almost as effective as RYGB in inducing weight loss and improving co-morbidities [ 26 ].…”
Section: Surgical Principles and Methodsmentioning
confidence: 99%
“…Das Verfahren ist komplett irreversibel. Randomisierte, kontrollierte Studien zur perioperativen und langfristigen Komplikationsrate fehlen bisher sowohl für Erwachsene als auch für Kinder und Jugendliche, weshalb dieses Verfahren sehr kontrovers diskutiert wird [18,19,21,22,23]. Es führt jedoch -nach bisheriger Studienlage -zu einem signifikanten Gewichtsverlust, der auf restriktiven als auch endokrinen Mechanismen beruht.…”
Section: Bariatrische Chirurgie Im Kindes-und Jugendalter: Operative unclassified
“…Erste Einzelfallberichte existieren über die laparoskopische Schlauchmagenoperation (LSG) im Jugend- [18,19] sowie im Erwachsenenalter [21,22,23]. Die Ergebnisse bis zu drei Jahren nach Operation sind vielversprechend, Langzeitergebnisse liegen aber bisher noch nicht vor.…”
Section: Schlussfolgerungunclassified